2020
DOI: 10.1186/s12992-020-00628-6
|View full text |Cite
|
Sign up to set email alerts
|

How donors support civil society as government accountability advocates: a review of strategies and implications for transition of donor funding in global health

Abstract: Background Global health donors are increasingly transitioning funding responsibility to host governments as aid budgets plateau or decline and countries meet development and disease burden goals. Civil society organizations (CSOs) can play a critical role as accountability mechanisms over their governments, but transitions raise questions about how donor-supported CSOs will fare following transition, especially in environments of limited political commitment. Decreases in funding may force CSOs to scale back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The implementation gap likely exists because governments are unwilling to directly confront the power dynamics that shape the right to SRH, and/or because many programmes are piloted by non-governmental actors and then not subsequently scaled up and taken over by governments. On the one hand, non-governmental actors may have greater expertise to both research and provide rights-based care, particularly to marginalised groups 145. On the other hand, in many settings, the government is the only actor with the capacity to implement health programmes at scale.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation gap likely exists because governments are unwilling to directly confront the power dynamics that shape the right to SRH, and/or because many programmes are piloted by non-governmental actors and then not subsequently scaled up and taken over by governments. On the one hand, non-governmental actors may have greater expertise to both research and provide rights-based care, particularly to marginalised groups 145. On the other hand, in many settings, the government is the only actor with the capacity to implement health programmes at scale.…”
Section: Discussionmentioning
confidence: 99%
“…Although donor funding makes tremendous contributions to healthcare delivery, countries dependent on donor funding have presented challenges. For example, donor funding is declining and there is a limited political will to take over the role of donors (Gotsadze et al 2019;McDonough & Rodríguez 2020). This state of affairs consequently affects health programmes supported by external funding.…”
Section: Funding In the Public Healthcare Delivery Sectormentioning
confidence: 99%
“…This flexibility was welcomed by agencies, and flexibility in development aid funding has previously been highlighted as a priority for donors and agencies. [18][19][20] However, flexibility was not universal, as participants also reported that some parts of funding were not permitted to be used for COVID-19 adaptations. Inflexibility of funding was reported to have led to stalled programs.…”
Section: Relationshipsmentioning
confidence: 99%